PENGARUH LEVERAGE, PROFITABILITAS, LIKUIDITAS DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Callista, Dyan; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this research to gain an empirical evidence on the influence of leverage, profitability, liquidity and investment decision variables on firm value in manufacturing companies sector consumer non-cylicals and healthcare listed on Indonesia Stock Exchange (IDX) period 2019-2021. This study used secondary data which was tested using SPSS version 29. This research used 19 companies that have been selected by purposive sampling method. The results obtained that leverage, profitability, liquidity and investment decision had a significant positive effect on firm value.